Death by capitalism in Eliot's The Waste Land. Issue 5 (4th May 2022) - Carver, Beci
ABSTRACT: This article is an attempt to construct a socialist Eliot, whose familiarity with German economic policy in the 1910s and 1920s exposed him to a version of socialist economics that caught his imagination. In this essay, I focus on the year that preceded Eliot's breakdown, when a number of significant mergers transformed British banking, concentrating the industry's power and wealth among a nucleus of 'Big Banks'. I understand Eliot to have witnessed the dawn of what Rudolf Hilderding terms 'finance capital', and to have recoiled in horror. I read 'Death by Water' as an elegy for a lost era in the history of capitalism, when, as Hilferding suggests, the dependence of economic systems on 'direct relationship[s] between members of society' made a version of 'socialist' banking thinkable.